Advancing infection control in Australasian medical ultrasound practice. Issue 1 (23rd February 2017) - Westerway, Susan Campbell; Basseal, Jocelyne M
Abstract: Introduction/Aims: Australasia is witnessing a rapidly increasing use of diagnostic medical ultrasound in clinical practice with industry statistics giving a conservative estimate of ten million scans performed annually in Australia and New Zealand. Ultrasound practice has broadened from its traditional use in radiology, obstetrics and gynaecology, vascular and cardiology specialties to embrace emergency medicine, rheumatology, midwifery, physiotherapy, paramedics and other point of care practice. With this expansion of practice comes an increase in the potential risk for ultrasound transmitted bacterial or viral infection due to suboptimal cleaning habits of transducers, cords and keyboards. Results/Conclusion: This study describes results of an Australasian survey on the disinfection and hygiene practice in medical ultrasound. Results highlighted a significant need for updated guidelines and education on infection prevention and control in medical ultrasound.